Expression of miR-15b-5p and toll-like receptor4 as potential novel diagnostic biomarkers for hepatitis C virus-induced hepatocellular carcinoma - Amal Ahmed Mohamed; Noha Nagah Amer; Noha Osama; Wael Hafez; Ali Elsaid Abdelrahman Ali; Mahmoud Maamoun Shaheen; Ayman Abd Alhady Alkhalegy; Eman Alsayed Abouahmed; Shamel Mohamed Soaida; Lamees A. Samy; Ahmed El-Kassas; Ivan Cherrez-Ojeda; et al. (Non-coding RNA Research, 2025)
Objectives: Globally, hepatocellular Carcinoma (HCC) ranks seventh in women's cancer and fifth in men's cancer. Early identification can minimize mortality and morbidity. MicroRNAs and Toll-like receptors have been suggested as potential new biomarkers for HCC; Therefore, we explored Toll-like receptor 4 (TLR-4) and miRNA 15b-5p as new non-invasive HCC biomarkers and early detection approaches. Methodology: In this case-control study, four primary groups were formed from 400 patients who participated in this study: 100 hepatitis C (HCV) patients without cirrhosis or HCC, 100 HCV with cirrhosis patients, 100 HCC and HCV patients, and 100 healthy controls. The HCC diagnosis was confirmed according to the American Association for the Study of Liver Disease (AASLD) Practice Guidelines. Triphasic computed tomography was used to assess the HCC tumor size. Real-time PCR was used to analyze miRNA 15b-5p and Toll-like receptor 4 (TLR-4) expression profiles. Results: Significant diagnostic performance was achieved by miRNA 15b-5p in differentiating the HCC group from the control group, with 90 % sensitivity and 88 % specificity (AUC] 0.935, p < 0.001), while TLR-4 had moderate diagnostic performance with 85 % sensitivity and 86 % specificity (AUC:0.885, p < 0.001). Conclusions: The ability of miR-15b-5p to recognize HCC was positive and it outperformed Toll-like receptor4. MiR-15b-5p has the potential to be a more precise and predictive biological marker for HCC than Toll-like receptor4. Future studies exploring different miRNAs and HCC cases from various etiologies are required to better understand the role of miRNAs in this disease and allow for more effective strategies.